Demands of an ethics of knowledge - Lucrecia Rovaletti, María (Acta Bioethica, 2002)
The desire of knowledge, one of man's most important goals, there are also mixed wishes of other type, like ambition or competition, which can deviate him from his uninterested objectives. That is why there are many people who throw a suspect on this libido sciendi that has become a libido dominandi where the legal valorization of power and the idolatry of progress are combined. It will be the ethic comisions or comites to play a calming function that can work as a boundary to this cultural anguish. However, these possible deviations must not only be atributed to the desire of knowing in itself, but to the social system, which, troughout the institutions, compels investigators to compete among themselves with projects and publications, and obliges them to enter either into an economic competition or into an international confrontation in order to obtain recognition. As members of a scientific comunity, with its own interests, it is necessary for us to defend the autonomy of this libido cognoscendi in front of those who take social decisions, in the measure that economical resources for investigation depend on them. Uninterested investigation is still very important for the cultural wellfare of society, but it is important to be on guard, as man is not only in the centre of investigations, but also of its applications.